Polski dyskurs patriotyczny w prasie i w pismach okolicznościowych z 2. połowy XVIII wieku - Siuciak, Mirosława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The article examines the process of shaping of the Polish patriotic discourse, which was determined by such events of the 18th century as the Bar Confederation, the Great Sejm proceedings, and the Kościuszko Uprising. In a situation in which Poland was threatened with the invasion of surrounding world powers and in the face of impending armed struggle for sovereignty, the then most important values uniting the Polish nation were formulated. The first entity to define them were the Bar confederates, who fought against the Russian army in defence of their fatherland, religion, freedom, and independence. In the 1790s the patriotic discourse shifted to the press covering the proceedings of the Great Sejm, and later to newspaper coverage of the Kościuszko Uprising. During these events, the freedom demands were altered because the conservative Sarmatian republicanism had been replaced with ‚new’ republicanism – characterised by social radicalism and supporting the separation of church and state. Despite some semantic shifts, for more than 200 years the most significant values constituting the Polish patriotic discourse have been: fatherland, freedom, and independence.